Butane encephalopathy. Issue 9 (19th August 2005) - Harris, D; Mirza, Z
Abstract : Volatile solvent abuse (VSA) is defined at the "intentional inhalation of a volatile substance for the purpose of achieving a euphoric state". The lifetime prevalence of VSA in the UK remains steady at around 15%, the fourth highest rate in Europe, and VSA is the most common form of drug abuse in the 11–15 year age group in England and Wales. A 13 year old girl presented to the accident and emergency unit following inhalation of butane based deodorant, which resulted in a prolonged semiconscious state with encephalopathic symptoms.